Meritocracy and the University Selective Admission in England and the United States - Mountford Zimdars, Anna (Bloomsbury Academic, 2016)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Who gets into elite universities, how and why? What are places like Harvard in the United States or Cambridge in England looking for when they admit undergraduate students? What qualities do selectors value and how do they decide between many applicants with often stellar attainment records? And, are we all better off because of who these elite universities admit? Meritocracy and the University provides an insight into the world of university admissions. Based on interviews with professional admissions staff and academic faculty members who select students, the book explains what selectors value and how they make decisions. By shining a light on the world of university admissions in England and in the United States, readers are invited to reflect on the similarities and differences in who selects and how selection is done, the purpose and mission of universities, and the challenges universities face in building fair admissions processes when earlier opportunities to shine in education are unequally distributed.